Embryological approach to the morphology of the ligamentum mucosum of the human knee joint - Gonera, B.; Borowski, A.; Zielinska, N.; Palac, W.; Paulsen, Friedrich; Olewnik, L. (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Purpose: The ligamentum mucosum is a ligamentous structure within the synovial layer of the knee joint capsule. It usually arises from the infrapatellar fat pad and is inserted into the intercondylar notch of the femur. In recent years, more attention has been paid to this structure because of its clinical significance. Despite the growing attention, the complex morphology of the ligamentum mucosum has led to many misunderstandings among the scientists and clinicians. Therefore, the main objective of this study was to characterize the morphology of the ligamentum mucosum and its attachment points, classify it, and evaluate its prevalence. Methods: Classical anatomical dissection was performed on 70 lower limbs of human fetuses fixed in 10% formalin solution. Morphology was carefully assessed, and morphometric measurements were performed. The types revealed were classified. Results: The ligamentum mucosum was present in 100% of all 70 specimens examined. Two types were detected. Type I (65.71%) - "cord-like". This type was the most common and is characterized by a single longitudinal ligament. The proximal attachment of the ligamentum mucosum was located in the middle of the infrapatellar fat, and the distal attachment was at the tip of the intercondylar notch. Type II (34.29%) - "vertical septum". This type is less common, but its morphology is much more complex compared to type I. It is wider and thicker than type I. Proximally, it is attached to the infrapatellar fat pad and distally through the entire intercondylar notch down to the anterior surface of the anterior cruciate ligament. It divides the joint cavity into medial and lateral sides. Conclusion: The ligamentum mucosum exhibits high morphologic variability, and the view that it is a vestigial remnant of the embryologic development of the knee should be reconsidered. We have proposed an anatomical classification of its types in human fetuses, which is a valuable addition to existing knowledge and will hopefully change the approach of clinicians and scientists.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Anatomical variations; Fetuses; Ligamentum mucosum; New classification